A case of voluntary tail autotomy in the snake Dendrophidion dendrophis (Schlegel, 1837) (Reptilia: Squamata: Colubridae) - Hoogmoe, Marinus Steven; Avila-Pires, Teresa Cristina Sauer (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
We report direct observation of voluntary tail autotomy in the Colubrid snake Dendrophidion dendrophis from Monte Dourado, Pará, Brazil. Voluntary tail autotomy for this species had been reported before, but the process itself never has been described.
Keywords: Brazil; Amazonas; Snake; Defensive behaviour; Tail autotomy